Simulation analysis of the retinal conformational equilibrium in dark-adapted bacteriorhodopsin - Baudry, Jérôme; Smith, Jeremy C. (Biophysical journal, 1999)
In dark-adapted bacteriorhodopsin (bR) the retinal moiety populates two conformers: all-trans and (13,15)cis. Here we examine factors influencing the thermodynamic equilibrium and conformational transition between the two forms, using molecular mechanics and dynamics calculations. Adiabatic potential energy mapping indicates that whereas the twofold intrinsic torsional potentials of the C13==C14 and C15==N16 double bonds favor a sequential torsional pathway, the protein environment favors a concerted, bicycle-pedal mechanism. Which of these two pathways will actually occur in bR depends on the as yet unknown relative weight of the intrinsic and environmental effects. The free energy difference between the conformers was computed for wild-type and modified bR, using molecular dynamics simulation. In the wild-type protein the free energy of the (13,15)cis retinal form is calculated to be 1.1 kcal/mol lower than the all-trans retinal form, a value within approximately kBT of experiment. In contrast, in isolated retinal the free energy of the all-trans state is calculated to be 2.1 kcal/mol lower than (13,15)cis. The free energy differences are similar to the adiabatic potential energy differences in the various systems examined, consistent with an essentially enthalpic origin. The stabilization of the (13,15)cis form in bR relative to the isolated retinal molecule is found to originate from improved protein-protein interactions. Removing internal water molecules near the Schiff base strongly stabilizes the (13,15)cis form, whereas a double mutation that removes negative charges in the retinal pocket (Asp85 to Ala; Asp212 to Ala) has the opposite effect.